Al Quran and Hadith Perspective Infaq - Muhammad Sofyan Tambunan (ISNU Nine-Star Multidisciplinary Journal, 2024)
Infaq is an important teaching in Islam regulated in the Qur'an and Hadith, which includes all forms of spending wealth in the way of Allah, both obligatory such as zakat and sunnah. Infaq has a deep spiritual and social dimension, aims to cleanse wealth and soul, and strengthen social solidarity in society. This study aims to examine the concept of infaq from the perspective of the Qur'an and Hadith, with a focus on its understanding and implementation in the lives of Muslims. The method used is normative juridical, by analyzing the verses of the Qur'an, relevant hadiths, and fiqh literature that discusses infaq. The results of the study show that infaq not only has high spiritual value but also functions as an important instrument in creating social justice and the welfare of the people. In conclusion, infaq is a very important form of worship in Islam that needs to be considered and practiced optimally in everyday life.